Environmental Policy Perspectives: Bridging the Gap in Recycling Used-Lead Acid Batteries in Bangladesh - Zaman, Atiq; Pacini, H. (2024)
Electric rickshaws, also known as E-rickshaws, have become essential components of Bangladesh's transportation infrastructure, significantly impacting the country's socio-economic fabric. Despite contributing approximately US $871 million to the local economy, concerns persist regarding the environmental and health implications of the used-lead-acid batteries (ULABs) industry, especially concerning battery recycling practices. This study undertakes a comprehensive examination of Bangladesh's national regulatory policies and standards, focusing primarily on ULABs. It identifies the various stakeholders involved in the e-rickshaw and battery industry and evaluates relevant national policies and standards. The study's main findings highlight significant disparities within the regulatory framework, primarily stemming from the lack of harmonization and comprehensive integration of ULABs-related policies at both national and international levels. Recognizing the crucial roles played by both the informal and formal sectors, the study emphasizes the need for formalization accompanied by appropriate subsidies and support to ensure occupational health and safety standards. Such measures are imperative to enhance industry compliance, competitiveness in local and international markets, and overall safety. Furthermore, the study identifies notable gaps in standards aimed at ensuring the minimum quality and performance of batteries produced from informally recycled lead-acid batteries. Ambiguity surrounding the legal status of the e-rickshaw sector due to a lack of clear mandates from regulatory bodies further complicates the regulatory landscape. The dispersion of ULABs-related regulations across multiple policies and acts exacerbates integration challenges, creating loopholes that may lead to mismanagement. In response, the study proposes a set of recommendations to address these challenges. Achieving a balance between economic imperatives and environmental stewardship in ULABs management requires the establishment of a harmonized regulatory framework, proactive engagement with stakeholders, and robust enforcement mechanisms. Implementing these recommendations has the potential to cultivate a more sustainable e-mobility ecosystem in Bangladesh, safeguarding both public health and environmental integrity.